1997
DOI: 10.1042/bj3230233
|View full text |Cite
|
Sign up to set email alerts
|

Actin is cleaved during constitutive apoptosis

Abstract: Proteases play an important role in the programme of cell death by apoptosis but little is known of the substrates cleaved, particularly in constitutive models of this type of cell death. Neutrophils spontaneously undergo apoptosis in culture without requiring external stimuli. During this process we found biochemical and immunochemical evidence for the cleavage of membrane-associated actin, a component of the cytoskeleton that links polymerized actin to the plasma membrane. Cleavage occurred at a single site … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
79
1
1

Year Published

1999
1999
2002
2002

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 133 publications
(88 citation statements)
references
References 46 publications
7
79
1
1
Order By: Relevance
“…To date, in human neutrophils, only the MFAP gelsolin was found to be a substrate for caspases (34). Actin is known to be cleaved during spontaneous neutrophil apoptosis, but this protein was not found to be a caspase substrate (62). Similarly, we found that the degradation of vinculin and ␣-and ␤-tubulin is not accelerated by VAA-I and that caspases do not seem to play an important role in their degradation during spontaneous apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…To date, in human neutrophils, only the MFAP gelsolin was found to be a substrate for caspases (34). Actin is known to be cleaved during spontaneous neutrophil apoptosis, but this protein was not found to be a caspase substrate (62). Similarly, we found that the degradation of vinculin and ␣-and ␤-tubulin is not accelerated by VAA-I and that caspases do not seem to play an important role in their degradation during spontaneous apoptosis.…”
Section: Discussionsupporting
confidence: 49%
“…The possibilities that LPS may induce calpain activation and that calpain activation may regulate cytoskeletal reorganization and motility are currently under investigation. An alternative possibility is that actin cleavage is a marker of neutrophil apoptosis (52).…”
Section: Table V Analysis Of Ph 55-67 Two-dimensional Page Gelsmentioning
confidence: 99%
“…Binding of FITC-conjugated annexin V in ice-cold PBS containing calcium and magnesium as previously described (18,20) was used to assess exposure of phosphatidylserine exposure. PI was used to assess plasma membrane permeability.…”
Section: Assessment Of Pmn Morphology and Flow Cytometric Analysismentioning
confidence: 99%